DAYA SAING KAKAO INDONESIA DI PASAR ASEAN PRA DAN PASKA PEMBERLAKUAN MASYARAKAT EKONOMI ASEAN - Rendy Alvaro; Robby Alexander Alexander (Pusat Kajian Anggaran, 2018)
The analysis of the competitiveness of Indonesian cocoa aims to convey Indonesian's cocoa export position amidst the ASEAN trades, particularly after two years of the establishment of ASEAN Economic Community. The research used three economic indicators in order to measure the competitiveness of Indonesian cocoa. These indicators are RCA (Revealed Comparative Advantage), EPD (Export Product Dynamics), and MS (Market Share). The three indicators were used in period of 2012 and 2017 in the ASEAN market. The results showed that the cocoa product with HS-180100, HS-180310, HS-180320 and HS-180500 code have competitiveness in Malaysia, Philippines and Singapore. However, the competitiveness of all types of cocoa has decreased after the implementation of ASEAN Economic Community.